Transgelin 2 is required for embryo implantation by promoting actin polymerization - Liang, Xiaoling; Jin, Yimei; Wang, Hao; Meng, Xinlu; Tan, Zhongzhou; Huang, Tao; Fan, Shangrong (The FASEB journal, 2019)
Infertility has been a great challenge in reproductive medicine. At least 40% of human pregnancy losses are clinically unrecognized and occur because of embryo implantation failure. Identification of the proteins and biochemical factors involved in embryo implantation and that are essential for crosstalk between the embryo and uterus can further increase female fertility rates. The actin cytoskeleton and actin-binding proteins (ABPs) are of great importance for cell morphology and rearrangement, which is crucial for trophoblast adhesion and invasion. However, the research on ABPs in embryo implantation is insufficient. In this report, we found that transgelin (TAGLN)2 is highly expressed in mouse blastocyst trophoblasts. Notably, inhibition of mouse blastocyst trophoblast TAGLN2 by lentivirus-mediated RNA interference significantly impaired embryo adhesion and implantation ability. Further in vitro experiments demonstrated that TAGLN2 knockdown with small interfering RNA observably decreased the invasion and migration abilities of human trophoblast cells. Immunofluorescence colocalization and microscale thermophoresis analysis showed that TAGLN2 directly binds to actin. In addition, knockdown of TAGLN2 in trophoblast cells resulted in a remarkable reduction in F-actin rather than G-actin. Our findings reveal an unidentified role of TAGLN2 in regulation of trophoblast invasion and adhesion by promoting actin polymerization.-Liang, X., Jin, Y., Wang, H., Meng, X., Tan, Z., Huang, T., Fan, S. Transgelin 2 is required for embryo implantation by promoting actin polymerization.